Noninvasive Ultrasound Monitoring of Embryonic and Fetal Development in Chinchilla lanigera to Predict Gestational Age: Preliminary Evaluation of This Species as a Novel Animal Model of Human Pregnancy. (27th May 2019) - Greco, A.; Ragucci, M.; Liuzzi, R.; Prota, M.; Cocchia, N.; Fatone, G.; Mancini, M.; Brunetti, A.; Meomartino, L.
Abstract : Ultrasound is a noninvasive routine method that allows real-time monitoring of fetal development in utero to determine gestational age and to detect congenital anomalies and multiple pregnancies. To date, the developmental biology of Chinchilla lanigera has not yet been characterized. This species has been found to undergo placentation, long gestation, and fetal dimensions similar to those in humans. The aim of this study was to assess the use of high-frequency ultrasound (HFUS) and clinical ultrasound (US) to predict gestational age in chinchillas and evaluate the possibility of this species as a new animal model for the study of human pregnancy. In this study, 35 pregnant females and a total of 74 embryos and fetuses were monitored. Ultrasound examination was feasible in almost all chinchilla subjects. It was possible to monitor the chinchilla embryo with HFUS from embryonic day (E) 15 to 60 and with US from E15 to E115 due to fetus dimensions. The placenta could be visualized and measured with HFUS from E15, but not with US until E30. From E30, the heartbeat became detectable and it was possible to measure fetal biometrics. In the late stages of pregnancy, stomach, eyes, and lenses became visible. Our study demonstrated the importance of employing both techniques while monitoring embryonic and fetal development to obtain an overall and detailed view of all structures and to recognize any malformation at an early stage. Pregnancy in chinchillas can be confirmed as early as the 15 th day postmating, and sonographic changes and gestational age are well correlated. The quantitative measurements of fetal and placental growth performed in this study could be useful in setting up a database for comparison with human fetal ultrasounds. We speculate that, in the future, the chinchilla could be used as an animal model for the study of US in human pregnancy.